Comparative real-world effectiveness and safety of super-bioavailable itraconazole 50 mg bd and 65 mg bd in the management of dermatophytosis - Mahadkar, Namrata; Dhoot, Dhiraj S.; Barkate, Hanmant (International Journal of Research in Dermatology, 2022)
In recent times, India has witnessed a steep surge in prescription of itraconazole in the management of dermatophytosis.1 But due to its pharmacokinetics, it has shown multiple variations in the results. To overcome these challenges, a newer itraconazole formulation i.e. super-bioavailable itraconazole (SBITZ) has been launched recently in India. Currently, there are 4 different strengths of SBITZ which are approved by DCGI.2,3 But there is no any clinical data regarding comparison of different strength of SBITZ. This retrospective analysis aimed to compare two different strengths of SBITZ; 50 mg and 65 mg in the management of dermatophytosis.